Biografia, informação e memória: um estudo a partir da autobiografia de Edson Nery da Fonseca - Rita de Cássia Gonçalves (2020)
This research aimed to investigate the biography genre in its dual function: source of information and memory document. Supported by a bibliographic review inscribed in multidisciplinary perspectives, it sought to apprehend the specifics of the biographical genre and characterize the productions derived from it, notably the biographies and autobiographies, both as a source of information and as a social resource for the production and dissemination of individual memories and historical information. In this sense, he adopted as an object of analysis the autobiography of Edson Nery da Fonseca aiming to rescue elements of his personal, professional life and the politicalintellectual contributions sanctioned by him to the field of Brazilian Librarianship. In methodological terms, the analysis took place through the hermeneutic apprehension of Edson Nery da Fonseca's autobiographical account, combined with the interpretative work of his intellectual biography. Instituted as the first plan of action, hermeneutic reading enabled us to understand, from the object of analysis in question, the main elements that shape what Philippe Lejeune defined as the Autobiographical Pact, to which he added, through the questions formulated around from the intellectual biography of Edson Nery da Fonseca elements that reveal his performance in the fields of culture and national librarianship, both as a theorist and as a political agent. As a result, the research carried out revealed the attributes of referentiality and breadth concerning autobiographies and biographies as sources of information and memories. Similarly, Edson Nery da Fonseca's autobiography proved to be a significant testimony to the history of Brazilian Library Science.